PKM Seminar Parenting Tangguh Di Era Milenial untuk Ibu Persit Kartika Chandra Kirana Makassar - Farida Aryani; Muhammad Rais; Fitriana Fitriana; Inayah Ridhayanti Qarimah; Maslina Maslina (Universitas Negeri Makassar, 2025)
Abstract. The rapid development of digital technology has transformed parenting paradigms, presenting new complexities for parents guiding children amidst a plethora of information and digital content. This study highlights the urgency of adequate preparation for parents, particularly members of Persit Kartika Chandra Kirana (the Indonesian Army Wives Association) within the military environment, who face unique challenges related to their husbands' dynamic professions. Initial observations in Makassar indicated a gap in emotional support due to these dynamics, potentially affecting psychological well-being and the quality of childcare. The concept of